1990
DOI: 10.1128/aem.56.9.2726-2735.1990
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Integrated Plasmids in the Chromosome of Lactococcus lactis

Abstract: Derivatives of plasmids pBR322, pUB110, pSC101, and pTB19, all containing an identical fragment of lactococcal chromosomal DNA, were integrated via a Campbell-like mechanism into the same chromosomal site of Lactococcus lactis MG1363, and the transformants were analyzed for the stability of the integrated plasmids. In all cases the erythromycin resistance gene of pE194 was used as a selectable marker. Transformants obtained by integration of the pBR322 derivatives contained a head-to-tail arrangement of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(73 citation statements)
references
References 31 publications
2
69
1
Order By: Relevance
“…However, it was found that the copy number of genes integrated at delta sites may decrease by gene loop-out events due to homologous recombination during long-term nonselective cultivation (Lee and Silva, 1997;Oliveira et al, 2007;Wang et al, 1996). Genetic instability under nonselective conditions was also reported after classical chromosomal integration of the target gene at a specific site (Leenhouts et al, 1990). To avoid this problem, improvements may be achieved by changing culture conditions, which may however not be feasible in industrial applications.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was found that the copy number of genes integrated at delta sites may decrease by gene loop-out events due to homologous recombination during long-term nonselective cultivation (Lee and Silva, 1997;Oliveira et al, 2007;Wang et al, 1996). Genetic instability under nonselective conditions was also reported after classical chromosomal integration of the target gene at a specific site (Leenhouts et al, 1990). To avoid this problem, improvements may be achieved by changing culture conditions, which may however not be feasible in industrial applications.…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, the counterstained cells were observed for microscopic assessment (Paik 1980). The total genomic DNA was extracted by the method described by Leenhouts et al (1990) with some modifications. For molecular identification, the amplification was carried by designing the genus specific primer pairs (Lactobacillus genus) that were; F: 5 0 AGAGTTTGATCMTG GCTCAG-3 0 and R: 5 0 -TACCTTGTTAGGACTTCACC-3 0 for direct amplification of 16S ribosomal RNA gene containing 1500 bp.…”
Section: Isolation Biochemical/molecular Identification and Probiotimentioning
confidence: 99%
“…Extraction of chromosomal DNA was achieved using the protocol of Leenhouts et al (1990). The primers LacAll-F (5 0 -TGCCTAATACATGCAAGTC-3 0 ) and LacAll-R (5 0 -CCTTGTTACGACTTCACC-3 0 ) were used to amplify nearly the full length of the 16S rRNA gene, corresponding to the conserved 16S rRNA gene regions of four type strains of vaginal Lactobacillus: Lactobacillus crispatus ATCC 33197 (AF257096); L. crispatus ATCC 33820 (AF257097); Lactobacillus jensenii ATCC 25258 (AF243176); and Lactobacillus vaginalis ATCC 49540 (AF243177).…”
Section: Taxonomic Identification Of Lactobacillus By 16s Rrna Gene Smentioning
confidence: 99%